Physical education and felt identities. Paradoxes between discipline and ideology - Guavita Ocampo, Carlos Orlando (2024)
This article reports on the results of a doctoral research that aimed to generate a theoretical approach to the paradoxes that arise from Physical Education in the face of gender diversity. Physical Education is based on science, common sense and observable evidence, it educates human beings in movement, hence the importance of revealing the meanings of the informants, given the penetration into the school of an ideology that uses gender as mark of felt identity and denies scientific knowledge. A qualitative approach was used, a hermeneutic phenomenological method within an interpretive paradigm. A semi-structured interview was applied as an instrument to three teachers with a degree in Physical Education, two of them linked to public education and the other to the deanship of Higher Education. As a result, it was found that Physical Education is an interdisciplinary pedagogical discipline with its own vision of the axiology of the human being and seven paradoxes that teachers must face were revealed.